Patient and provider barriers to effective management of gout in general practice: a qualitative study. Issue 9 (22nd March 2012) - Spencer, Karen; Carr, Alison; Doherty, Michael
Abstract : Objectives: To explore patient and provider illness perceptions and barriers to effective management of gout in general practice. Design and setting: A qualitative study involving semistructured face-to-face interviews with patients and health professionals from 25 Nottinghamshire general practices and one central National Health Service hospital. Participants: Twenty gout sufferers and 18 health professionals (six general practitioners, five hospital physicians, seven practice nurses). Results: A number of key themes emerged suggesting that several factors impact on patients' access to recommended treatments. The main barriers were patient experiences and lay beliefs of their condition which affected seeking advice and adherence to treatment. There was universal lack of knowledge and understanding of the causes and consequences of gout and that it can be treated effectively by lifestyle change and use of urate lowering therapy (ULT). All participants associated gout with negative stereotypical images portrayed in Victorian cartoons. Many viewed it as self-inflicted or part of ageing and only focused on managing acute attacks rather than treating the underlying cause. The main provider barriers that emerged related to health professionals' lack of knowledge of gout and management guidelines, reflected in the suboptimal information they gave patients and their reluctance to offer ULT as a 'curative' long-term management strategy. Conclusion: There are widespread misconceptions and lack of knowledge among both patients and health professionals concerning the nature of gout and its recommended management, which leads to suboptimal care of the most common inflammatory joint disease and the only one for which we have 'curative' treatment.